Multiculturalism transformation in the technological age: Challenges and opportunities - Habibah, Siti Maizul; Kartika, Rika; Rizqi, Ascosenda Ika (C-DISC, 2023)
This article discusses the transformation of multiculturalism in the technological age,focusing on the challenges and opportunities. Technology's ability to connect people from different cultural backgrounds extends the reach of multiculturalism, enabling the exchange of ideas, values, andexperiences. However, challenges suchas cultural appropriation and differing interpretations can threaten respect for cultural diversity. Unequal access to technology can lead to inequalities in cultural participation and digital literacy, widening the gap between social groups. To meet this challenge,efforts are needed to ensure equal access to technology and digital inclusion for all groups. However, the technological age also offers opportunities for multiculturalism. Digital technology can be a tool to promote constructive intercultural dialogue, increase knowledge of other cultures and builddeeper understanding. It is important to develop applications and platforms that strengthen fair and respectful cultural exchange. To meet the challenges and seize the opportunities, holistic policies and approaches are needed to develop multiculturalism in the technological age. Governments, civilsociety organizations and civil society must work together to promote digital inclusion, support digital and intercultural literacy, and develop regulations that encourage the responsible use of technology.